A 20-year (1996–2015) trend in deaths as a result of burns in the Transkei subregion of South Africa. (July 2018) - Meel, Banwari L
Background: Deaths as a result of burns are unrecognised, under-reported and therefore under-estimated, especially in rural areas such as the Transkei subregion of South Africa. Burning to death is painful and preventable. Objective: The aim of this study was to investigate a 20-year trend in deaths as a result of burns in the Transkei subregion of South Africa. Method: A record review descriptive study was undertaken of all medico-legal autopsies performed from 1996 to 2015 at Mthatha Forensic Pathology Laboratory. Results: In total 22, 952 medico-legal autopsies were conducted at Mthatha Forensic Pathology Laboratory from 1996 to 2015. Of these, 689 (3%) were burn related. This gives an average of eight deaths resulting from burns per 100, 000 of the population annually in this region. The highest rate (11.6/100, 000) was recorded in 2007, and the lowest (3.3/100, 000) in 2004. Males outnumbered females at a ratio of 1.6:1. Young children of aged 10 years old or younger accounted for 130 of the victims, amounting to a death rate of 1.51/100, 000. Conclusion: The number of deaths as a result of burning has more than doubled in the last 20 years (1996–2015) in the Transkei subregion of South Africa. Action to prevent these deaths is urgently required.